Alif’s Adolescence Crises in Ahmad Fuadi’s The Land of Five Towers (Jurnal Pembelajaran Sastra, 2020)
This study aims to describe the crisis of adolescents in the main character in Ahmad Fuadi's The Land of Five Towers. This research shows the adolescence crises that occurred on the main character in the novel The Land of Five Towers and the efforts made by the main character to overcome the adolescence crises. This research is categorized into literary criticism. The objective is to analyze a literary work using literary theories. The object of this study is novel The Land of Five Towers by Ahmad Fuadi. This research focuses on adolescence crises that occur in the main character psychosocially. The researcher uses the theory of psychosocial development by Erik H. Erikson but focus only on the adolescence stage. The data in this study are taken from quotes in the novel in the form of author's explanation of the main character and dialogue between characters. The results showed the following things. First, the form of adolescent crisis experienced by the main character, Alif, in the form of an identity crisis and role confusion. The identity crisis experienced by Alif is shown by finding a different personality with others, the emergence of feelings of doubt and worry, and the emergence of feelings of jealousy and envy. While role confusion experienced by Alif was shown by low self-esteem when dealing with people who were different from him, feeling confusion to adjust to be accepted by society or community, and feeling confused when he wanted to determine or give his role in a society. or community. Second, the efforts made by Alif in overcoming the adolescent crisis are diverse. In overcoming his identity crisis, Alif motivated himself, being optimistic, and showing his identity. Then Alif's efforts in overcoming role confusion are by accepting his identity and the environmental situation, accepting the role given by others, and accepting messages or advice of others. These efforts are obtained from within themselves and the support of others.